Utilization of lactose hydrolysed paneer whey for the preparation of Buttermilk - Singh, Trishul Prakash; Nath, B. Surendra; Veena, N; Pushpadass, Heartwin Amaladhas; Emerald, F Magdaline Eljeeva (Indian Journal of Dairy Science, 2019)
The objective of this work was to utilize concentrated and lactose hydrolyzed paneer whey (CLHPW) by partial substitution of milk for the preparation of buttermilk and to characterize for sensory and physico-chemical properties of buttermilk samples. Lactose in the concentrated paneer whey was hydrolyzed upto 55% using β–galactosidase and adjusted to 12% total solids was utilized in the preparation of four different formulations of buttermilk (6.6% solids) by its incorporation into milk before fermentation (F1 and F2) or fermented separately and then blended (F3 and F4), with the milk solids to whey solids (MS:WS) content adjusted to 1:1 and 1:2. Results indicated that formulations F1 and F3 (MS:WS, 1:1) had similar sensory characteristics as control buttermilk (F1), however, formulations F2 and F4 (MS:WS, 1:2) were significantly differ in color, consistency and overall acceptability scores from that of control. Results of physicochemical properties showed that formulations F1 and F3 had significantly higher viscosity and consistency values but lower phase separation compared to the formulations F2 and F4. Based on the results of sensory and physicochemical properties, buttermilk (F3) prepared by blending of fermented CLHPW and dahi (MS:WS, 1:1) was highly acceptable and could replace the milk solids with whey solids up to 50%. This study helps to utilize the whey and its valuable nutrients besides reducing the problem of environmental pollution caused due to its disposal.